2012
DOI: 10.1186/1472-698x-12-30
|View full text |Cite
|
Sign up to set email alerts
|

Moving from ideas to action - developing health financing systems towards universal coverage in Africa

Abstract: BackgroundAccelerating progress towards universal coverage in African countries calls for concrete actions that reinforce social health protection through establishment of sustainable health financing mechanisms. In order to explore possible pathways for moving past the existing obstacles, panel discussions were organized on health financing bringing together Ministers of health and Ministers of finance with the objective of creating a discussion space where the different perspectives on key issues and needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 12 publications
0
38
1
Order By: Relevance
“…The only other literature commenting on these issues in the African context that could be located is a paper based on a series of panel discussions between Ministries of Finance and Health [31]. The key message from these panel discussions was the need for Ministries of Health to build an evidence base on the need for investment in the health sector and to demonstrate efficient use of resources within the health sector.…”
Section: Discussionmentioning
confidence: 99%
“…The only other literature commenting on these issues in the African context that could be located is a paper based on a series of panel discussions between Ministries of Finance and Health [31]. The key message from these panel discussions was the need for Ministries of Health to build an evidence base on the need for investment in the health sector and to demonstrate efficient use of resources within the health sector.…”
Section: Discussionmentioning
confidence: 99%
“…75 The consequences of inefficiency are anything but trivial: it has been estimated for OECD countries that improving efficiency to the standard of best performing countries would bring, on average, an increase of 2 years in life expectancy, compared with 4 months brought by a 10% increase in public health expenditure per capita. 167 Investing in efficiency and demonstrating value can strengthen the dialogue between African Ministries of Health and Ministries of Finance 168 and help convince Ministers of Finance of the returns associated with allocating much needed resources for health.…”
Section: Improving Health Spending Efficiencymentioning
confidence: 99%
“…In this respect, the weakness in planning is twofold, firstly, the lack of costed strategic plans to inform resource mobilisation efforts and secondly, the limited funding posing a challenge to planning. A panel discussion between ministers of health and ministers of finance from African countries concluded that the lack of clearly articulated priorities detailed in evidence‐based and costed plans explained the prevailing unsatisfactory financing for health . Relatedly, Namibial et al argue that the limited funding in itself is a challenge to good planning.…”
Section: Discussionmentioning
confidence: 99%
“…Past efforts in resource mobilisation have yielded varied results, and in majority of cases, not much success has been registered. Cited challenges include poor prioritisation, contradictions in the policy direction, inefficiencies in resource allocation and use, and inadequacies in the consultative processes . These are partially attributed to flaws in the planning processes.…”
Section: Introductionmentioning
confidence: 99%